2016
DOI: 10.18535/jmscr/v4i12.132
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Clinical Presentation and Outcome of Concurrent Malaria and Dengue Infection from a Malaria Endemic Zone of North India

Abstract: This study has been done to differentiate clinical and biological parameter of co-infections from infections alone and to find out whether patients infected by both malaria and dengue were more severe than either infection alone. Material and Methods: All febrile adult patients (> 18 years of age) were investigated for malaria, dengue and other causes of fever. Patients of concurrent dengue and malaria (Group A) were compared with malaria mono-infection (Group B) and dengue mono-infection (Group C). Frequencie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Another finding that the current study can report is the high prevalence of co-infection and malaria mono-infection in rural areas which is also the same observation that was found in random houses. Our finding concurred with a study in India [26] whose found maximum cases from rural areas in co-infection and malaria monoinfection.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Another finding that the current study can report is the high prevalence of co-infection and malaria mono-infection in rural areas which is also the same observation that was found in random houses. Our finding concurred with a study in India [26] whose found maximum cases from rural areas in co-infection and malaria monoinfection.…”
Section: Discussionsupporting
confidence: 93%
“…Analysis on the symptoms of all patients has shown fever to be the commonest symptom (100%) in all the three groups. This result was similar to what has been found in Pakistan and in India [12,26].…”
Section: Discussionsupporting
confidence: 92%
“…Overall, 9 studies met the eligibility criteria [ 11 , 13 – 15 , 25 29 ]. Additional searches through Google scholar retrieved four additional studies [ 30 33 ], resulting in 13 studies included in the present study.
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“… Sonkar et al, 2019, [ 32 ] India (2018) Cross-sectional observational study NA 994 patients with febrile illness P. falciparum (16), P. vivax (13), mixed infection (1) NA/279 NA/685 17/30 Jaundice (12), bleeding (5) NA 17/30 13. Verma et al, 2016, [ 33 ] India (2015) Prospective observational study Adult (> 18 yrs) Male (256), female (84) 340 patients with febrile illness NA 38/156 CNS involvement (2), bleeding (32), respiratory distress (4) *hypotension (28) 63/132 CNS involvement (12), bleeding (4), hypotension (4), respiratory distress (20), severe anaemia (20), death (3) 27/52 Bleeding (8), hypotension (3), respiratory distress (4), severe anaemia (12) 12/52 Bleeding (8), respiratory distress (4), *hypotension (3) 26/52 impaired consciousness (9), multiple convulsions (1), prostration (2), shock/hypotension (19), hypoglycaemia (0), jaundice (21), pulmonary oedema (1), bleeding (42), metabolic acidosis or acute respiratory distress (4), severe anaemia (14), and acute renal failure (3) Shock (7), respiratory distress (4), severe bleeding (58), renal failure (3), impaired consciousness (9), multiple convulsions (1), jaundice (39) * Severe cases defined by authors ** n / N : Out of N confirmed cases, there are a total of n severe cases; NA: not applicable a WHO malaria- Severity Criteria for Malaria from World Health Organization, 2014 b WHO dengue- Severity Criteria for Dengue from World Health Organization, 2009 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation